Photostable Red-Emitting Fluorescent Rhein-Magnesium(Ⅱ) Coordination Polymer Nanodot-Based Nanostructures With a Large Stokes Shift for Imaging Mitochondria in Cancer Cell - Jiang, Qin; Du, Ke; Jiang, Yuhang; Liu, Yuhan; Han, Chen; Yin, Zhihui; Wang, Ying; Gao, Xiaoyan (Frontiers in Oncology, 2021)
The mitochondria play a significant role in many cellular processes and are recognized as one of the most important therapeutic targets in cancer. Direct long-term imaging of the mitochondria is very crucial for treating cancer. However, the development of a red-emitting mitochondrial probe with a large Stokes shift and photostability remains highly challenging. Fluorescent metal complexes with superior physicochemical property have emerged as new fluorescent nanomaterials due to their increasing advantages in bioimaging. Herein, a luminescent pitaya-type nanostructure based on rhein-magnesium(II) (Rh-Mg) coordination polymer nanodots was used as a fluorescent nanoprobe to selectively image the mitochondria benefiting from the introduction of triphenylphosphine. The as-prepared Rh-Mg nanodot-based nanoprobe showed red emission peaking at 620 nm, a large Stokes shift (100 nm), and excellent photostability as compared with commercial mitochondrial probes. Due to these extraordinary features, this fluorescent nanoprobe was successfully used for mitochondrial targeting imaging of live cancer cell line Neuro-2a (mouse neuroblastoma) and BV2 microglial cells. Therefore, our results pave a new way for the design of fluorescent nanoprobes for imaging mitochondria in cancer cell.